Renal Presentation in Pediatric Acute Leukemia: Report of 2 Cases. Issue 37 (September 2015) - Sherief, Laila M.; Azab, Seham F.; Zakaria, Marwa M.; Kamal, M.; Elbasset Aly, Maha Abd; Ali, Adel; Alhady, Mohamed Abd
Abstract : Abstract: Renal enlargement at time of diagnosis of acute leukemia is very unusual. We here in report 2 pediatric cases of acute leukemia who had their renal affection as the first presenting symptom with no evidences of blast cells in blood smear and none of classical presentation of acute leukemia. The first case is a 4-year-old girl who presented with pallor and abdominal enlargement. Magnetic resonance imaging showed bilateral symmetrical homogenous enlarged kidneys suggestive of infiltration. Complete blood picture (CBC) revealed white blood count 11 × 10 9 /L, hemoglobin 8.7 g/dL and platelet count 197 × 10 9 /L. Bone marrow aspiration was performed, and diagnosed precursor B-cell ALL was made. The child had an excellent response to modified CCG 1991 standard risk protocol of chemotherapy with sustained remission, but unfortunately relapsed 11 month after the end of therapy. The second child was 13-month old, presented with pallor, vomiting, abdominal enlargement, and oliguria 2 days before admission. Initial CBC showed bicytopenia, elevated blood urea, creatinine, and serum uric acid, while abdominal ultrasonography revealed bilateral renal enlargement. Bone marrow examination was done and showed 92% blast of biphenotypic nature. So, biphynotypic leukemia with bilateral renal enlargement and acute renal failure was subsequently diagnosed. The patients admitted to ICU and received supportive care and prednisolone. Renal function normalized and chemotherapy was started. The child achieved complete remission with marked reduction of kidney size but, unfortunately she died from sepsis in consolidation phase of therapy. This case demonstrates an unusual early renal enlargement in childhood acute leukemia. Renal involvement of acute leukemia should be considered in child presenting with unexplained bilateral renal enlargement with or without renal function abnormalities and bone marrow examination should be included in the workup.